Materials 2005
DOI: 10.1115/imece2005-80846
|View full text |Cite
|
Sign up to set email alerts
|

Microcellular PP-CaCO3 Nanocomposites: Relationship Between Nanocomposite Morphology and Foam Morphology

Abstract: Polymeric nanocomposites exhibit high potential as a new material for carbon dioxide (CO2) foaming. In this paper, a polypropylene (PP)/nano-calcium carbonate (nano-CaCO3) composite was selected to investigate the relationship between nanocomposite morphology and foam morphology. Nanocomposites were prepared using a twin-screw extruder with screw including both shearing and mixing elements. Nanocomposites with different morphology via changing the nano-CaCO3 content were then foamed by using supercritical CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The aforementioned results may be explained as follows. First, the nanoparticles dispersed in the PP and HDPE phases (as shown in Figure 5) play a role as heterogeneous nucleating agents [10,16,17], thus providing more sites for cell nucleation. Especially in exfoliated claybased nanocomposites and well-dispersed CaCO 3 -based nanocomposites, the nanoparticles with their extremely fine dimensions provide a much larger interfacial area between particles and polymer matrix to facilitate the cell nucleation.…”
Section: Effect Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned results may be explained as follows. First, the nanoparticles dispersed in the PP and HDPE phases (as shown in Figure 5) play a role as heterogeneous nucleating agents [10,16,17], thus providing more sites for cell nucleation. Especially in exfoliated claybased nanocomposites and well-dispersed CaCO 3 -based nanocomposites, the nanoparticles with their extremely fine dimensions provide a much larger interfacial area between particles and polymer matrix to facilitate the cell nucleation.…”
Section: Effect Of Nanoparticlesmentioning
confidence: 99%
“…The visual observation by Taki et al [8] showed that the nanoclay can improve the cellular structure of foamed PP by enhancing the nucleation and retarding the growth of bubbles in the early stage of foaming. Very recently, using a pressure vessel as the foaming apparatus, Huang and Wang [9,10] improved the foamability of PP by blending it with HDPEs and incorporating the nano-calcium carbonate (nano-CaCO 3 ) particles into it and its blends with HDPE.…”
Section: Introductionmentioning
confidence: 99%